LAPORAN ARUS KAS METODE LANGSUNG SEBAGAI ALAT PREDIKSI ARUS KAS OPERASIONAL MASA DEPAN - , Bety Nur Achadiyah, S.Pd ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this study is to examine the ability of direct cash flow statement in predicting future cash flow. This study is conducted to evaluate FASBâs statements in SFAS 95 and IAIâs statements in PSAK No. 2, that the direct method provide more useful information in predicting future cash flow than indirect method. The panel data regression models are developed by regarding the efficient regression model. This study evaluates the two cash flow models. The first model consists of direct cash flow components whereas the second model consists of indirect components. The sample of this study is manufacturing companies listed in Indonesia Stock Exchange within the period of 1999-2005. The data is collected using purposive sampling method. The amount of the sample is 82 companies in 7 years, so obtain 754 observations. The result of this study shows that model consisting direct cash flow components has better prediction ability than model consisting indirect cash flow components. The empirical result supports the FASBâs and IAIâs statements, that direct method provide more useful information in predicting cash flow than indirect method.